TI_GERICHTE 32.2009.202 vom 9. Oktober 2009 , Richiesta di prestazioni respinta in assenza di un grado di invalidità pensionabile - TI Tribunale d'appello (2009)
Richiesta di prestazioni respinta in assenza di un grado di invalidità pensionabile